Certain Distance-Based Topological Indices of Parikh Word Representable Graphs. (25th May 2021) - Thomas, Nobin; Mathew, Lisa; Sriram, Sastha; Nagar, Atulya K.; Subramanian, K. G.
Abstract : Relating graph structures with words which are finite sequences of symbols, Parikh word representable graphs (PWRGs) were introduced. On the other hand, in chemical graph theory, graphs have been associated with molecular structures. Also, several topological indices have been defined in terms of graph parameters and studied for different classes of graphs. In this study, we derive expressions for computing certain topological indices of PWRGs of binary core words, thereby enriching the study of PWRGs.